2019
DOI: 10.31849/lectura.v10i1.2409
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Digital Storytelling on Students’ Speaking Ability

Abstract: Speaking is an assential skill that used be mastered by the Students, because it is necessary for them to improve their ability to communicate orally by presenting their ideas and opinions in real life. Digital storytelling is the practice of using computer-based tools to tell stories. It can be used as homework, classroom group projects, or a holiday project for students. In relation to this, the purpose of the research is to find out is there any significant effect of digital storytelling on students’ speaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Five previous studies have the same topic as the present study (Ivala, Gachago, Condy & Chigona, 2013;Hedderman, 2019;Foelske,, 2014;Idayani, 2019;Lazareva & Cruz-Martinez, 2020). Almost all of the topics of previous studies are similar to the present study, i.e.…”
Section: Introductionsupporting
confidence: 78%
“…Five previous studies have the same topic as the present study (Ivala, Gachago, Condy & Chigona, 2013;Hedderman, 2019;Foelske,, 2014;Idayani, 2019;Lazareva & Cruz-Martinez, 2020). Almost all of the topics of previous studies are similar to the present study, i.e.…”
Section: Introductionsupporting
confidence: 78%
“…According to that earlier study, it is because the use of this media gives more opportunity for the students to be more active and creative in explaining the content orally. Idayani (2019), who also carried out their own research, came to the same conclusion. Students have the opportunity to enhance their communication abilities by using digital storytelling as a tool to do so.…”
Section: Journal Of English Teaching and Researchmentioning
confidence: 53%
“…Similarly, Yuksel et al (2011) showed digital storytelling helps students enhance their language abilities, particularly their written and spoken speaking and narrative skills, as well as their foreign language pronunciation. Furthermore, Idayani (2019) shows that teachers can use digital storytelling as a medium to improve students' speaking abilities, especially in terms of vocabulary, pronunciation, grammar, comprehension, and fluency. The use of digital storytelling can increase students' motivation to speak English.…”
Section: Introductionmentioning
confidence: 99%